Nutrient flows in agricultural production and international trade: Ecological and policy issues - Eric T. Craswell; Ulrike Grote; Julio Henao; Paul L. G. Vlek (University of Bonn, Center for Development Research (ZEF), 2004)
This paper addresses the issue of environmental and ecological impacts of nutrient flows within and between countries by reviewing and presenting data on nutrient balances and global nutrient movements. The results for nutrient depletion in agricultural soils during 1996-1999 show that in most countries in Africa and Latin America and the Caribbean rates of depletion are so high that current land use is not sustainable. At the other end of the scale, nutrient surplus derived from agriculture is most serious in the USA and industrialized countries of Europe, but also occurs in some densely populated areas of countries such as India and China. International net flows of NPK in traded agricultural commodities were estimated to total 4.8 Tg in 1997 and predicted to increase to 8.8 Tg in 2020. Flows vary widely across regions. Major net importers of NPK are West Asia/North Africa and China. Although soils in countries of Sub-Saharan Africa are widely known to be heavily degraded due to nutrient depletion, this region is nevertheless a net importer of NPK in agricultural commodities. However, the nutrients imported in food and feed commodities to Sub-Saharan countries are commonly concentrated in the cities creating waste disposal problems rather than alleviating deficiencies in rural soils. Countries with a net loss of NPK in agricultural commodities are the major food exporting countries the United States, Australia, and some countries of Latin America. A wide range of policy measures influence agricultural trade, nutrient flows and balances. The effects of agricultural trade liberalization and the reduction of production subsidies are briefly described, as well as more direct environmental policies like nutrient accounting schemes, eco-labeling, and nutrient trading. Our study highlights the need for environmental costs to be factored into the debate on nutrient management and advocates more interdisciplinary research on these important problems.
Keywords: 380; Environmental Economics and Policy; Ernährung; Stoffstrommanagement; Agraraußenhandel; Handelsliberalisierung; Landwirtschaft; Nachhaltige Entwicklung; Welt